TOURISM ATTRACTION IN TANJUNG SETIA BEACH AS A DESTINATION OF MARINE TOURISM IN KRUI, PESISIR BARAT DISTRICT, LAMPUNG - Sintia Alwamy (Sean Institute, 2023)
This research aims to introduce the attractions of Tanjung Setia Beach in Krui, Pesisir Barat Sub-district, Lampung, as a marine tourism destination. The purpose of this study is to obtain an overview of Tanjung Setia Beach and its attractions. The method used in this study is a qualitative approach with descriptive analysis method using primary data obtained from field surveys and secondary data in the form of documentation from reliable sources such as online news media, publications from the Tourism Department, and supporting research journals.Tanjung Setia Beach in Pesisir Barat Regency, Lampung, is a marine tourism destination with strong appeal and potential as an attractive tourist spot. The beach offers extraordinary natural beauty, and its large and powerful waves make it an ideal destination for surfers. Tanjung Setia Beach can be easily accessed, and the amenities or facilities available are sufficient. With proper efforts, Tanjung Setia Beach can become an appealing and memorable tourist destination for visitors.